Pectins - Extraction, Purification, Characterization and Applications 2020
DOI: 10.5772/intechopen.85629
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Wine Polysaccharides

Abstract: Polysaccharides are the main macromolecules of colloidal nature in wines, and play a fundamental role in the technological properties and organoleptic characteristics of the wines. The role of the different wine polysaccharides will depend on their quantity but also on their chemical composition, molecular structure and origin. Wine polysaccharides originate from grapes and yeast acting during the winemaking. The main polysaccharides present in wines can be grouped into three major families: (i) polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 124 publications
(174 reference statements)
0
28
0
Order By: Relevance
“…Polysaccharides increase the density and body of the wine, modulating the astringency perception. In addition, polysaccharides are able to interact with volatile compounds [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides increase the density and body of the wine, modulating the astringency perception. In addition, polysaccharides are able to interact with volatile compounds [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MP enrichment of wines have been proven to modify wine astringency and sucrosity [ 105 , 106 ]. MPs have also been mentioned to play an important role in tartrate salt crystallization, although the MP concentration needs to be adjusted depending on the wine considered [ 107 , 108 , 109 ]. Additionally, recent studies have shown that MPs can interact with all anthocyanin families and modulate the bioaccessibility of polyphenolic compounds during digestion in the gastrointestinal tract [ 110 ].…”
Section: What Could Be the Consequences For The Winemaker Or The Wine Lover?mentioning
confidence: 99%
“…They constitute a group of glycoproteins which, along with β-linked glucans and chitin, form the major components of the yeast cell wall [ 1 ]. In the well-studied genus Saccharomyces , the glycan moiety of mannoproteins consists mostly of mannose (>90%) and glucose, as well as N-acetyl-glucosamine and mannosylphosphate (0.1–1%), with a protein content ranging between 1% and 10% [ 2 , 3 ]. Their molecular weight may vary between 5 and 800 kDa, although the typical reported range is 50–500 kDa [ 3 ].…”
Section: Introductionmentioning
confidence: 99%